Ion‐Implant Isolated Vertical GaN p‐n Diodes Fabricated with Epitaxial Lift‐Off From GaN Substrates. Issue 4 (18th December 2018) - Wang, Jingshan; McCarthy, Robert; Youtsey, Chris; Reddy, Rekha; Xie, Jinqiao; Beam, Edward; Guido, Louis; Cao, Lina; Fay, Patrick
Abstract : Ion‐implant isolated vertical GaN p‐n junction diodes fabricated with epitaxial lift‐off (ELO) from GaN substrates are demonstrated. For the ELO process, a band‐gap selective photoelectrochemical (PEC) wet etch with a pseudomorphic InGaN release layer is utilized. Compared with devices isolated using mesa etching, the ion‐implant isolated devices exhibit more ideal forward current–voltage characteristics and lower leakage currents. Devices are also compared with and without ELO processing. Devices measured after ELO processing and mounting to metallized carrier substrates show similar electrical performance to GaN‐on‐GaN control samples without ELO processing. No indication of material quality degradation is found on the ELO devices. The ELO devices exhibit turn‐on voltages of 3.15 V (at a current density of 100 A cm −2 ), with specific on resistance (Ron ) of 0.52 mΩ cm 2 at 4.8 V and breakdown voltage (Vbr ) approximately of 750 V. Abstract : Vertical GaN p‐n diodes fabricated with band‐gap selective photoelectrochemical wet etching lift‐off process enables homoepitaxial growth for low‐defect‐density devices. Nearly identical performance to control devices on GaN substrates and no indication of material quality degradation is found. It provides a possible routine to achieve flexible thin‐film power electronics with high performance and low cost.